Anxiety and depression in Multiple Sclerosis (MS): Antecedents, consequences, and differential impact on well-being and quality of life - Hanna, Mariam; Strober, Lauren Beth (Multiple sclerosis and related disorders, 2020)
•Depression and anxiety are both common in multiple sclerosis (MS).•Despite their high prevalence and comorbidity, greater attention has been given to depression in MS.•Much less is known about the impact and risk factors of anxiety in MS.•The present investigation was conducted to develop a better understanding of the impact of depression, anxiety and comorbid depression and anxiety on disease symptoms, disease management, psychological well-being, and quality of life in MS.•We also examined the demographic and disease-related risk factors associated with depression and anxiety and the role of social support and substance use. Individuals with multiple sclerosis (MS) are often plagued by the unpredictability of their disease and have to contend with uncertainty in their life and significant life changes. This can lead to high levels of stress, perceived lack of control, helplessness, and anxiety. Despite these circumstances, anxiety disorders are often overshadowed by depression, which can result in its presence being overlooked and undertreated by many medical professionals. One hundred and eighty three individuals with MS completed a comprehensive online survey assessing depression and anxiety and the demographic and disease risk factors of such, including social support and substance use. Participants also completed measures of MS symptomatology, disease management, psychological well-being, and quality of life to determine the impact of depression and anxiety on outcomes associated with MS. Findings suggest that both depression and anxiety are prevalent in MS and related to many outcomes. However, based on comparisons of the associations and group comparisons, with a few exceptions, anxiety proved to more impactful than depression when examining these outcomes. When evaluating the risk factors/contributors of anxiety and depression, social support was a consistent predictor. Younger age and shorter disease duration were also associated with anxiety, while lower education and substance use were predictors of depression. Findings suggest that attention to anxiety be given as much as depression as it plays a large role in individuals’ perceived health and well-being, which subsequently impacts the severity of symptoms and overall quality of life. Early identification of anxiety and potential substance use and increased social support also appear to be crucial for mitigating the impact of depression and anxiety.